Alcohol and cardiovascular mortality in Moscow; new evidence of a causal association. Issue 12 (December 1998) - Chenet, L; McKee, M; Leon, D; Shkolnikov, V; Vassin, S
Abstract : BACKGROUND: In explaining recent trends in Russian mortality, alcohol drinking has often been put forward as a major factor. However, cardiovascular disease remains the major cause of death in Russia and alcohol is currently viewed as having a protective effect on heart disease. This study explores this apparent paradox by examining daily trends in deaths from cardiovascular disease in Moscow. SUBJECTS: Those dying in Moscow in the years 1993-1995. METHODS: Analysis of daily variation in deaths based on data from Moscow City death certificates. RESULTS: There is a significant increase in deaths from alcohol poisoning, accidents, and violence and cardiovascular diseases on Saturdays, Sundays, and Mondays. This is especially marked for sudden deaths. This pattern is consistent with the known pattern of drinking in Russia, which is more likely to take place in binges than is the case in other countries. CONCLUSION: A possible causative role for alcohol in sudden cardiovascular death is suggested as there are no other obvious explanations for this pattern, which cannot be accounted for by daily variations in traditional risk factors such as smoking or lipids. Although this is inconsistent with the prevailing view in the West that alcohol is seen as cardioprotective, there is considerable supporting evidence from a necropsy study and from studies in other places with a similar pattern of drinking. In countries such as Russia, where patterns of drinking differ considerably from that in the West, binge drinking can be an important cause of sudden cardiac death. This has important implications for estimates of the amount of mortality worldwide attributable to specific risk factors and thus for national and international policy.